Differences in Opinion on Healthy and Junk Food Between Generation Y and Generation Z - Devani, Pushti; Gandhi, Rahil; Vidani, Jignesh (MultiTech Publisher, 2024)
Consumption of both healthy and junk food is becoming a major public health concern, especially among younger generations. In Ahmedabad, India, this study looks at the perspectives of two generations on the choice between junk food and healthy food: Generation Z (born 1997–2012) and Generation Y (born 1981–1996).A survey regarding these food categories was administered to [number of respondents] individuals of both generations to assess their attitudes, opinions and consumption patterns. The aim of the data analysis, which used [the technologies described], was to find significant differences in their health knowledge, influencing factors and preferences. The results increase our knowledge of generational differences in food preferences and guide focused initiatives aimed at encouraging better eating practices in Generation Y and Generation Z